Stiva Cave: A New Discover Of Prehistoric Hominid Underwater Cave - Danni Gathot Harbowo; Stiva Alouw; Theresia Gerungan Soetamanggala; Azalia Gerungan (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
Stiva Cave is an underwater cave (15,3 m below recent sea level), which located in Nusa Penida, Bali, Indonesia. Nusa Penida is a Karst landscape island in southern Bali Island. No many underwater caves are known and explored in this area, Stiva Cave is a first underwater cave which explored and discovered in Nusa Penida area. In this cave we found a number of fossils that we identified as vertebrate fossil and unique process that very potential for geotourism, especially for fun diving tourism. We mapped entire cave tunnel and measure a safety and risk for scuba diving, then we identified the fossil. At the result, there a several risk that need to be aware and several safety procedures that must be allow for observer. In other way, we found many similar fossils that and it spread in different tunnel that very potential for education in geotourism. We suggest that this cave is a shelter for hominid species when Last Glacial Maximum happens, before 21.000 years ago